Traffic Accident Risk Assessment and Blackspot Identification on Urban Roads in Pontianak City Using the Equivalent Accident Number Method - Azwansyah, Heri; Umar, Umar (Jurnal Teknik Sipil, 2026)
Traffic accidents remain a critical challenge in urban transportation systems, particularly on arterial corridors with high traffic volumes. This study aims to evaluate traffic accident risk and identify accident-prone locations on Veteran Street and Pahlawan Street in Pontianak City, Indonesia. Traffic accident data from 2019 to 2023 were obtained from official records of the Pontianak City Police. Accident vulnerability was analyzed using the Accident Rate method to measure accident intensity per road length and the Equivalent Accident Number (EAN) method to incorporate accident severity through weighted casualty indicators. The Upper Control Limit (UCL/BKA) method was applied to determine statistical thresholds for identifying accident blackspots. Results show that both Veteran Street and Pahlawan Street have accident rate values exceeding 1.0, indicating that these corridors are categorized as accident-prone roads. Two segments were identified as significant blackspots: the 0.230–0.460 km segment on Veteran Street and the 0.000–0.175 km segment on Pahlawan Street, where EAN values exceed the BKA threshold. The findings highlight priority locations for traffic safety improvements and provide an empirical basis for infrastructure enhancements, traffic control measures, and enforcement strategies to reduce accident risk in urban road networks.